Cocconeis tortilis: a new marine diatom (Bacillariophyta, Cocconeidaceae) from Japan - Suzuki, Hidekazu; Nagumo, Tamotsu; Tanaka, Jiro (Phytotaxa, 2014)
A new species of Cocconeis, C. tortilis, was found on some seaweed collected from the Izu and Okinawa Islands of Japan. Its morphology was examined using both light and electron microscopy; details are described herein. This small diatom is characterized by: 1) a concave raphid valve with a straight raphe inclined from the apical axis, central area forming stauros, and uniseriate striae consisting of circular areolae occluded by hymens: 2) a twisted convex araphid valve with a narrow lanceolate sternum inclined from the apical axis, and uniseriate striae consisting of several loculate areolae occluded by hymens: and 3) a cingulum consisting of three non fimbriated girdle bands including a valvocopula.